Respuestas
Respuesta dada por:
6
Sean a y b las incognitas.
a+b=5
a*b=-84
De la primera podemos decir que:
a=5-b
Sustituyendo en la segunda:
(5-b)*b=-84
5b-b^2 = -84
0 = b^2 - 5b - 84
Factorizando:
0 = (b+7) (b-12)
Entonces:
b = -7
b = 12
Si b = -7
Entonces a:
a=5-(-7)
a = 12
Por lo tanto b = -7 y a = 12
a+b=5
a*b=-84
De la primera podemos decir que:
a=5-b
Sustituyendo en la segunda:
(5-b)*b=-84
5b-b^2 = -84
0 = b^2 - 5b - 84
Factorizando:
0 = (b+7) (b-12)
Entonces:
b = -7
b = 12
Si b = -7
Entonces a:
a=5-(-7)
a = 12
Por lo tanto b = -7 y a = 12
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años